2019
DOI: 10.1242/jeb.194019
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking and pivotal individuals during the reunification of ant colonies

Abstract: Maintenance of a social group requires the ability to reach consensus when faced with divisive choices. Thus, when migrating colonies of the ant Temnothorax rugatulus split among multiple sites, they can later reunify on the basis of queen location or differences in site quality. In this study, we found that colonies can reunify even without obvious cues to break the symmetry between sites. To learn how they do so, we observed both symmetric reunifications (between identical nests) and asymmetric reunification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…73,74 In particular, our study species features a caste of significantly larger soldier ants, and this may lead to the natural scenario described above. In such a scenario, as in our experiments, a colony reunification in the better nest at a later time (as described in other studies 38,[75][76][77] ) is impossible. Rather, our findings lead us to predict that under these circumstances, the majority of ants would concede the better choice and unite with the rest in an inferior nest.…”
Section: Discussionsupporting
confidence: 53%
“…73,74 In particular, our study species features a caste of significantly larger soldier ants, and this may lead to the natural scenario described above. In such a scenario, as in our experiments, a colony reunification in the better nest at a later time (as described in other studies 38,[75][76][77] ) is impossible. Rather, our findings lead us to predict that under these circumstances, the majority of ants would concede the better choice and unite with the rest in an inferior nest.…”
Section: Discussionsupporting
confidence: 53%
“…Experimental studies on the speed-accuracy trade-off showed that colonies often split in urgent emigrations, but they also noted that split colonies were eventually able to reunite (Franks et al, 2003a, 2009). Later studies (Doering and Pratt, 2019, 2016; Doering et al, 2020) showed that artificially divided colonies readily re-unite, using the same behavioral tools as in emigrations, but relying more on the efforts of a small group of active workers. These findings suggest that emigrations depend on a mixture of individual and colony-level decision making.…”
Section: New Predictionsmentioning
confidence: 99%
“…Although successful, models of this process have been limited to the simple challenge of choosing between two distinct and equidistant nests in a con-trolled laboratory environment. Real colonies face more complex scenarios, such as selecting among several sites of varying quality, avoiding splits when candidate nest sites are identical, and resolving colony splits when they occur (Doering and Pratt, 2019;Sasaki and Pratt, 2012). It also remains unclear how the colony maintains high performance with noisy and heterogeneous individuals, and how individuals modify their behavior to account for changes in context or colony state.…”
mentioning
confidence: 99%
“…Consequently, most model predictions have been limited to the simple challenge of choosing between two distinct and equidistant nests in a controlled laboratory environment. Real colonies face more complex scenarios, such as selecting among several sites of varying quality, avoiding splits when candidate nest sites are identical, and resolving colony splits when they occur (Sasaki and Pratt, 2012;Doering and Pratt, 2019).…”
Section: Introductionmentioning
confidence: 99%